Jasmonic Acid, Not Salicyclic Acid Restricts Endophytic Root Colonization of Rice - Chen, Xi; Marszałkowska, Marta; Reinhold-Hurek, Barbara (Frontiers in Plant Science, 2020)
Research on the interaction between the non-nodule-forming bacterial endophytes and their host plants is still in its infancy. Especially the understanding of plant control mechanisms which govern endophytic colonization is very limited. Here, we set out to determine which hormonal signaling pathway controls endophytic colonization in rice, and whether the mechanisms deviate for a pathogen. We used the endophyte Azoarcus olearius BH72 - rice model to investigate root responses to endophytes and compared it to the recently established pathosystem of rice blight Xanthomonas oryzae pv. oryzae PXO99 (Xoo) in flooded roots. In the rice root transcriptome, 523 or 664 genes were found to be differentially expressed in response to Azoarcus or Xoo colonization, respectively; however, the response was drastically different, with only 6% of the differentially expressed genes (DEGs) overlapping. Overall, Xoo infection induced a much stronger defense reaction than Azoarcus colonization, with the latter leading to down-regulation of many defence related DEGs. Endophyte-induced DEGs encoded several enzymes involved in phytoalexin biosynthesis, ROS (reactive oxygen species) production or PR proteins. Among putative plant markers related to signal transduction pathways modulated exclusively during Azoarcus colonization, none overlapped with previously published DEGs identified for another rice endophyte, Azospirillum sp. B510. This suggests a large variation in responses of individual genotypic combinations. Interestingly, the DEGs related to jasmonate (JA) signaling pathway were found to be consistently activated by both beneficial endophytes. In contrast, the salicylate (SA) pathway was activated only in roots infected by the pathogen. To determine the impact of SA and JA production on root colonization by the endophyte and the pathogen, we employed rice mutants with altered hormonal responses: mutant cpm2 deficient in jasmonate synthesis, and RNAi knockdown lines of NPR1 decreased in salicylic acid-mediated defense responses (NPR1-kd). Only in cpm2, endophytic colonization of Azoarcus was significantly increased, while Xoo colonization was not affected. Surprisingly, NPR1-kd lines showed slightly decreased colonization by Xoo, contrary to published results for leaves. These outcomes suggest that JA but not SA signaling is involved in controlling the endophyte density in roots and can restrict internal root colonization, thereby shaping the beneficial root microbiome.